1993
DOI: 10.1182/blood.v82.9.2649.2649
|View full text |Cite
|
Sign up to set email alerts
|

The heparin binding PECAM-1 adhesion molecule is expressed by CD34+ hematopoietic precursor cells with early myeloid and B-lymphoid cell phenotypes

Abstract: The platelet-endothelial cell adhesion molecule-1 (PE-CAM-1), defined by the CD31 monoclonal antibody (MoAb), was initially described as a cell-cell adhesion molecule mediating both homotypic and heterotypic adhesion. In this report, we show that enriched CD34+ human hematopoietic progenitor cell populations, containing early myeloid, erythroid, and multipotential progenitor cells, are CD31+. Analyses of CD34+ cell lines representing early myeloid, multipotential, and pre- pre-B-lymphoid progenitors indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(50 citation statements)
references
References 70 publications
4
46
0
Order By: Relevance
“…18,20 Another possible mechanism of recruitment could be modification of HSC homing and transmigration caused by changes in their microenvironment, potentially induced by the use of heparin during LVL. [21][22][23] In pediatric patients, however, only a few studies have been conducted that show the recruitment of CD34+ cells in low weight children to be significantly higher with LVL compared with conventional volume procedures. As such, apart from the well-known influence of the preapheresis CD34+ cell count, there are still only two established factors in pediatric patients that have a major impact on the CD34+ cell yield: the patient's diagnosis and volume of blood processed.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 Another possible mechanism of recruitment could be modification of HSC homing and transmigration caused by changes in their microenvironment, potentially induced by the use of heparin during LVL. [21][22][23] In pediatric patients, however, only a few studies have been conducted that show the recruitment of CD34+ cells in low weight children to be significantly higher with LVL compared with conventional volume procedures. As such, apart from the well-known influence of the preapheresis CD34+ cell count, there are still only two established factors in pediatric patients that have a major impact on the CD34+ cell yield: the patient's diagnosis and volume of blood processed.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, CD34 + cells express very late activation antigen-4 (VLA-4), VLA-5, and leukocyte function-associated antigen-1 (LFA-1) receptors. ICAM-1, ICAM-3, CD44, LFA-3, and PECAM-1 are also constitutively expressed by these cells [77,78]. Receptor expression and density may also vary according to the maturational status of the CD34 + cell and may play a major role in the release of these cells into the circulation.…”
Section: Adhesion Of Cd34 + Bone Marrow Cells To Bmscsmentioning
confidence: 99%
“…Characterization of PECAM-1 expression during early hematopoietic development (17) has shown that the protein is strongly expressed on enriched CD34+ human hematopoietic progenitor populations which contain multipotential progenitor cells, early myeloid and erythroid cells, stromal macrophages, and on CD34+ cell lines representing precursors of both the myeloid and B-lymphoid lineages. Bone marrow cells and cell lines which do not express CD34, and therefore represent more mature stages of all lineages, also demonstrated greatly reduced expression of PECAM-1 (17). The expression of PECAM-1 is then upregulated during terminal myeloid differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Watt el af. (17) speculated that PECAM-1 might play a central role in the regulation of hematopoiesis by selection of the appropriate hematopoietic microenvironments through 1) homotypic PE-CAM-1 interactions of precursor cells with stromal cells or endothelial cells, 2) heterotypic interactions with heparan sulfate proteoglycans, and 3) enhancement of adhesion through pl integrins, which are expressed on CD34+ cells.…”
Section: Introductionmentioning
confidence: 99%